Important Factors Applicable in Bilateral Relationships and Conflict Resolution - Rayamajhi, Yadav Bahadur (Journal of APF Command and Staff College, 2023)
Important factors applicable in bilateral relationships and conflict resolution are strategies, models, theories, and policies. In simple term, strategy is a long-term plan intended to achieve. An example to follow or imitate is a model. An idea to justify a course of action is a theory whereas law, regulation, and procedure used is a policy. Strategy embodies interest based priorities, which has short, medium, and long-term implications for a country. Model gives template that guides in constructing a system. Theory is essential tool for state craft. Guidance, constancy, accountability, efficiency, and clarity on how an organization operates are provided by policies. The objective of the paper is to examine important factors applicable in bilateral relationships and conflict resolution and highlight important relevant factors. To prepare the paper, qualitative methodology, explanatory research design, descriptive and analytical study design, and secondary sources of related textual and virtual documents are used. .After discussion, relevant strategies of ‘progressive nationalism, frequent dialogues and visits at high level, border diplomacy, pushing into regular constructive dialogues, playing diplomatic roles by a third country, and using International Boundary Research Unit (IBRU);’ models of ‘geo-economic and territorial project model of cross-border integration, bilateral trade flows, and partial settlement in resolving disputes;’ theories of ‘FDI inflow and bilateral political relationships, problem workshops, creation of international regime, and international organizations (IOs) brokered bargaining;’ and policies of ‘bilateral relationships, defense diplomacy, bilateral economic relations, bilateral diplomacy, nonalignment with equal friendships for all and diversification, an equal and respectful but not reciprocal relationships, leaders’ visits and diplomatic conflicts, third party intermediaries, enduring rivalries, pursuit of legal settlement, compromise or escalation or maintenance of status quo or swapping of territory, and uti possidentis or ground realities are highlighted to be adopted by the governments.